Guessing about Guessing: Practical Strategies for Card Guessing with Feedback. Issue 7 (9th August 2022) - Diaconis, Persi; Graham, Ron; Spiro, Sam
Abstract: In simple card games, cards are dealt one at a time and the player guesses each card sequentially. We study problems where feedback (e.g., correct/incorrect) is given after each guess. For decks with repeated values (as in blackjack where suits do not matter), the optimal strategy differs from the "greedy strategy" (of guessing a most likely card each round). Further, both optimal and greedy strategies are far too complicated for real-time use by human players. Our main results show that simple heuristics perform close to optimal.